2012
DOI: 10.1371/journal.pone.0029826
|View full text |Cite
|
Sign up to set email alerts
|

Access to Barrier Perches Improves Behavior Repertoire in Broilers

Abstract: Restriction of behavioral opportunities and uneven use of space are considerable welfare concerns in modern broiler production, particularly when birds are kept at high densities. We hypothesized that increased environmental complexity by provision of barrier perches would help address these issues by encouraging perching and enhancing use of the pen space across a range of stocking densities. 2,088 day-old broiler chicks were randomly assigned to one of the following barrier and density treatment combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
127
5
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(146 citation statements)
references
References 27 publications
11
127
5
3
Order By: Relevance
“…A similar pattern for perching behavior has been reported in other studies (Pettit-Riley and Estevez, 2001;LeVan et al, 2000). Ventura et al (2012) also reported a general trend for different density treatments (8, 13, and 18 birds m −2 ) that perching increased up to the fourth week and then declined. Hongchao et al (2013) reported an average of 7.4 % perching, with the maximum perching ratio occurring at the fifth week comparable to the current study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A similar pattern for perching behavior has been reported in other studies (Pettit-Riley and Estevez, 2001;LeVan et al, 2000). Ventura et al (2012) also reported a general trend for different density treatments (8, 13, and 18 birds m −2 ) that perching increased up to the fourth week and then declined. Hongchao et al (2013) reported an average of 7.4 % perching, with the maximum perching ratio occurring at the fifth week comparable to the current study.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were reported by Pettit-Riley and Estevez (2001), Estevez et al (2002), and Ventura et al (2012). Although Zhao et al (2013) reported beneficial effects of cooled perching on feed conversion ratio and body weight gain, these effects were related to a thermoregulatory advantage of the cooled perches.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found no significant effect of group size on the overall number of disturbances of resting or preening birds, indicating that larger group sizes per se, in the absence of a corresponding increase in bird density (Febrer et al, 2006;Ventura et al, 2012), did not cause birds to interrupt the behaviour of others more often. Although birds were more clustered in space in smaller groups, their behaviour was also more synchronised, reducing the chance that resting and preening birds would be disturbed by more active birds.…”
Section: Discussionmentioning
confidence: 61%